2017
DOI: 10.17352/2455-5479.000021
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Medication Adherence among hypertensive Patients in a Tertiary Health Center: A Cross-Sectional Study

Abstract: Introduction: Medication non-adherence is a major hindrance in the treatment of hypertension in Sub Saharan Africa. It is a major modifi able contributor to poor blood pressure control and complications of the disorder. An understanding of the factors that are associated with drug adherence in hypertension will contribute positively to the overall planning of public health educational programs on hypertension. Methods: This study was cross sectional and descriptive in nature conducted in the medical outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
4
15
3
3
Order By: Relevance
“…In the current study, more than three quarters of the study patients were categorized as non‐adherent, which represents a real threat for health outcomes in patients with angina in Jordan. The current study finding is consistent with the previous research in the Arab world and the Western countries which indicated that patients with CVD poorly adhere to their prescribed medications . In general, medication adherence rate in patients with CVD has varied widely across different studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, more than three quarters of the study patients were categorized as non‐adherent, which represents a real threat for health outcomes in patients with angina in Jordan. The current study finding is consistent with the previous research in the Arab world and the Western countries which indicated that patients with CVD poorly adhere to their prescribed medications . In general, medication adherence rate in patients with CVD has varied widely across different studies.…”
Section: Discussionsupporting
confidence: 91%
“…The current study finding is consistent with the previous research in the Arab world and the Western countries which indicated that patients with CVD poorly adhere to their prescribed medications. [12,[22][23][24][25] In general, medication adherence rate in patients with CVD has varied widely across different studies. While only 24% of the patients were found to be adherent in one study, [26] another study showed that 69.2% were adherent to their medications.…”
Section: Discussionmentioning
confidence: 99%
“…Data was obtained using a semi-structured questionnaire designed by one of the authors (E_ABA) after reviewing similar studies [6] [9] [11] [15] [16]. The full methodology of the study has been reported elsewhere (see appendix) [20]. Data on selected sociodemographic characteristics and lifestyle behaviors including smoking, drinking and use of herbal/traditional medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Poor glycemic control has been related to factors such as modality of treatment, age, gender, access to care, diet, obesity, systolic blood pressure, physical activity and level of knowledge of patients and their care givers [5] [6] [12] [14] [15] [17]. In many Nigerian communities, there is a high rate of herbal-medication use as well as poor knowledge attitude and practice of diabetes [4] [5] [6] [20].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In Nigeria, most of the patients (90.1%) sometimes forget to take their medications or do not bring their medications along when they leave home (94.3%). 39 Running out of drug is the second most important cause of nonadherence in our study population. Most of these antihypertensive drugs are expensive, and if patients from low socioeconomic condition fail to collect it free of cost from the hospital.…”
Section: Methods-mentioning
confidence: 87%